A Pasung Case during Twenty Years of Batak Man in Simalungun District, North Sumatera, Indonesia - Saragih, Fenny; Effendy, Elmeida (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: In 2019, the Government of Indonesia prioritized mental health programs to achieve a country that is free from pasung of psychiatric patients. Whereas based on Basic Health Research, The North Sumatra province since 2017 had 315 cases of people with hallucination, delusion, suspiciousness, confused and disturbed thoughts, and a total of 25 patients have been pasung by their own family. CASE PRESENTATION: Here, we report one case adult individual who was pasung for 20 years by his poor family in Simalungun District, North Sumatera, Indonesia. He is 41 years old, who never gets formal education at school, has no wife and friends, and who lives with his mother and two brothers. Disorders appeared 20 years ago when he was lost his father, who also likes him were diagnosed with schizophrenia. After his father died, he has many strange behaviors like talk and laughs by himself, anger without cause, hit his family, and when he meets other people besides his family, he immediately attacked them with any objects around him like stones or chopper. CONCLUSION: Pasung on psychiatric patients does not cure them but instead increases mental disorders that occur in patients. Family support is needed for patients to heal and prevent recurrence includes support assessment, instrumental, informational, and emotional support.